2011
DOI: 10.1021/ac202343e
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo, Transcutaneous Glucose Sensing Using Surface-Enhanced Spatially Offset Raman Spectroscopy: Multiple Rats, Improved Hypoglycemic Accuracy, Low Incident Power, and Continuous Monitoring for Greater than 17 Days

Abstract: This paper presents the latest progress on quantitative, in vivo, transcutaneous glucose sensing using surface enhanced spatially offset Raman spectroscopy (SESORS). Silver film over nanosphere (AgFON) surfaces were functionalized with a mixed self-assembled monolayer (SAM) and implanted subcutaneously in Sprague-Dawley rats. The glucose concentration was monitored in the interstitial fluid of six separate rats. The results demonstrated excellent accuracy and consistency. Remarkably, the root mean square error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
136
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 44 publications
0
136
0
Order By: Relevance
“…[83] The device was found to actively work over 17 days and more importantly the authors reported that between days 6 and 17, the glucose levels measured were found to lie within the clinically relevant levels. [83] This elegant and sophisticated example is a significant step forward in the development of a method by which diabetes sufferers could monitor and control their condition more accurately. [83] A similar format was also used to monitor lactate quantitatively.…”
Section: Sers and In Vitro Applications For The Detection Of Diseasementioning
confidence: 96%
See 2 more Smart Citations
“…[83] The device was found to actively work over 17 days and more importantly the authors reported that between days 6 and 17, the glucose levels measured were found to lie within the clinically relevant levels. [83] This elegant and sophisticated example is a significant step forward in the development of a method by which diabetes sufferers could monitor and control their condition more accurately. [83] A similar format was also used to monitor lactate quantitatively.…”
Section: Sers and In Vitro Applications For The Detection Of Diseasementioning
confidence: 96%
“…[60] Later work by the same group has strived to further develop this method for in vivo sensing. [81][82][83] In the initial stages the sensors (as described above) were implanted into animal models and the glucose levels were successfully measured via SERS and surface enhanced spatially offset Raman spectroscopy (SESORS) respectively. [81][82][83].…”
Section: Sers and In Vitro Applications For The Detection Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The glucose was successfully monitored in the interstitial fluid using SORS at clinically relevant levels. This pioneering experiment was subsequently extended by demonstrating a viability of monitoring of glucose levels in multiple rats (6) over a 17 day period with improved glycaemic index accuracy [73]. The rootmean-square error of calibration (RMSEC) (3.6 mg/ dL) and the root-mean-square error of prediction (RMSEP) (13.7 mg/dL) for low glucose concentration (< 80 mg/dL) was lower than the current International Organization Standard (ISO/DIS 15197) requirements.…”
Section: Glucose Detectionmentioning
confidence: 99%
“…In vivo transcutaneous SESORS glucose calibration and validation data sets on rat for a 5-day period. 22) Measurements from day 1 and 2 (blue ◆) were used for calibration sets. Measurements from day 3 (red •) and 4 (red ○) and 5 (red+) were used for validation sets.…”
mentioning
confidence: 99%